(untitled) (De la Crítica, 2023)
In Falconian literature we find religious elements that are linked to the regional idiosyncrasy. Regardless of the faith that is professed, as believers; The religious exists as a substratum that permeates the literature of those who write in this region. Many writers show in their works symbolic elements of their religious beliefs, which they have received through their education and with respect to which there is identification or rejection, evident in their texts. On this occasion, we will inquire into a novel writer, for which it is proposed to analyze the religious and spiritual vision, from the perspective of hope. Wilmara Borges, during her pilgrimage in the text Rare Colors, although she is sometimes discouraged, constantly shows elements that come to her as if sent by a supreme being. Belief in a deity supposes conferring a spiritual state on matter, a degree of faith that exceeds what is scientifically verifiable